River-Floodplain Interactions - Nutrient Concentrations in the Lower Parana River - Villar, Carlos Alberto (1998)
Fil: Villar, Carlos Alberto. Instituto de Limnología Dr. Raúl A. Ringuelet (ILPLA). Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina